Moisture sources and synoptic to seasonal variability of North Atlantic water vapor isotopic composition. Issue 12 (24th June 2015) - Steen‐Larsen, H. C.; Sveinbjörnsdottir, A. E.; Jonsson, Th.; Ritter, F.; Bonne, J.‐L.; Masson‐Delmotte, V.; Sodemann, H.; Blunier, T.; Dahl‐Jensen, D.; Vinther, B. M.
Abstract The isotopic composition of near surface (or planetary boundary layer) water vapor on the south coast of Iceland (63.83°N, 21.47°W) has been monitored in situ between November 2011 and April 2013. The calibrated data set documents seasonal variations in the relationship between δ18O and local humidity (ppmv) and between deuterium excess and δ18O. These seasonal variations are attributed to seasonal changes in atmospheric transport. A strong linear relationship is observed between deuterium excess and atmospheric relative humidity calculated at regional sea surface temperature. Surprisingly, we find a similar relationship between deuterium excess and relative humidity as observed in the Bermuda Islands. During days with low amount of isotopic depletion (more enriched values), our data significantly deviate from the global meteoric water line. This feature can be explained by a supply of an evaporative flux into the planetary boundary layer above the ocean, which we show using a 1‐d box model. Based on the close relationship identified between moisture origin and deuterium excess, we combine deuterium excess measurements performed in Iceland and south Greenland with moisture source diagnostics based on back trajectory calculations to establish the distribution of d‐excess moisture uptake values across the North Atlantic. We map high deuterium excess in the Arctic and low deuterium excess for vapor in the subtropics and midlatitudes. This confirms the role of North Atlantic water vapor isotopes as moisture origin tracers.